PENGARUH TEKNIK ASSERTIVE TRAINING UNTUK MENINGKATKAN KEMATANGAN HUBUNGAN SOSIAL SISWA KELAS X SMAN 8 PEKANBARU - Mahrani, Uci; Yakub, Elni; Umari, Tri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the effect of assertive training techniques to improve the maturity of social relations of class X students of SMAN 8 Pekanbaru. This research was conducted at SMAN 8 Pekanbaru for 3 months. This type of research uses quantitative research with an experimental method using the One-Group Pretest-Posttest Design research design. The measuring instrument used in this study is the social relations maturity measurement scale which consists of 81 items before the validity, and after divalidity there are 47 valid items with validity of 0.344 and reliability of 0.925. Determination of the subject using purporsive sampling technique, and get the subject of 7 grade X students of SMAN 8 Pekanbaru who identified as having a low level of social relations mortality. The data analysis technique used is the non parametric statistical technique using the Wilcoxon analysis test. The results of the study proved that the research hypothesis was accepted. This is known from